The Importance of World Englishes in Language Education - Nusratovich, Amonov Sunatillo (Researchparks Publishing, 2023)
In the context of teaching, the use of World Englishes has become increasingly relevant as it allows language teachers to have different approach to language education and a better understanding of the diverse backgrounds of students. Recognizing and valuing the diverse linguistic and cultural backgrounds of students is highly important for creating a more effective and engaging learning environment. Furthermore, understanding varius forms of spoken English around the world has a strong likelihood to deepen the understanding of the cultures and societies in which they are spoken.